A Lateral Flow Method for Aflatoxin B1 in Dry Dog Food: An Inter-Laboratory Trial. (21st January 2021) - Vudathala, Daljit; Cummings, Margie; Tkachenko, Andriy; Guag, Jake; Reimschuessel, Renate; Murphy, and Lisa
Abstract: Background: Dogs are highly susceptible to aflatoxins, the mycotoxins which most commonly cause acute dog illnesses and deaths following the consumption of contaminated food. Objective: In this study, a screening method to detect aflatoxin B1 (AFB1) in dry dog food was further evaluated at the FDA action level of 20 ng/g. A fourth-round multi-laboratory trial was performed. In contrast to the previous work, a different source of dog food was used in the multi-laboratory trial and more participants were involved. Method: The tested lateral flow method employs a modified procedure of the "Rosa ® AFQ-Fast Test Kit" from Charm Sciences Inc. A total of 60 unfortified blank study samples, 220 study samples fortified at 20 ng/g, and 80 study samples fortified at 9–11 ng/g were prepared by an independent party and analyzed in 10 collaborating laboratories in a blinded manner. Results: The pass rates were 98.3 and 94.5% for unfortified and 20 ng/g fortified study samples, respectively. Conclusions: The method is suitable for aflatoxin B1 screening at the FDA action level of 20 ng/g in a complex matrix such as dry dog food. Highlights: This work completes extensive method performance evaluation through four rounds of multi-laboratory trials.